COMPARISONAL ANALYSIS STUDY OF POWER LOSS AT THE CONNECTION POINT OF PIERCHING CONNECTOR WITH LINE TAP CONNECTOR ON 220 V LOW VOLTAGE NETWORK AT PT. PLN (PERSERO) ULP STABAT - Pungkas Setia Wibawa; Adi Sastra P Tarigan; Solly Aryza (INFOKUM, 2022)
The distribution system is divided into primary and secondary distribution networks. The primary distribution network is a network from substation transformers (GI) to distribution substations, while the secondary distribution network is a channel network from distribution substation transformers to consumers or loads. The primary distribution network is better known as the medium voltage network (JTM 20kV) while the secondary distribution network is the low voltage network (JTR 220/380V). The distribution network is the part of the electric power system that is closest to the customer or the load compared to the transmission network. At this time PT. PLN (Persero) experienced a power loss that occurred at the connection point of the low voltage network (JTR) on the use of a piercing connector. This study is to analyze the calculation of power loss on a low voltage network (JTR) by comparing the measurements between the input and output at the connecting point of the piercing connector with the line tap connector. With these conditions, it is necessary to evaluate and analyze for re-planning that takes into account planning criteria such as voltage drops and takes into account power losses for the sake of continuity of electricity services so that optimization appears on the network used.